The Comparison of Variant Index Score (VIS) of Homemade and Commercial Lyophilized Serum - Ilma Ainun Nisa; Amalia Putri Khurota Ayyun; Anik Handayati; Museyaroh; Suhariyadi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Many laboratory installations have not implemented quality assurance periodically due to the high cost of purchasing control materials. This study aims to determine the difference in Variant Index Score value of homemade lyophilized serum with commercial parameters of SGOT, SGPT, creatinine, BUN, glucose, uric acid, triglycerides, and cholesterol. The research was conducted in January–May 2023 at the Surabaya Health Center laboratory, the reference laboratory, and the Ubaya Technobiology Faculty using descriptive comparative research with a quantitative approach. The test material used was homemade lyophilized serum, with the research variable being the VIS value of lyophilized serum. The results of the analysis showed a comparison of the VIS value of homemade and commercial serum based on the participant's target values of SGOT, SGPT, creatinine, BUN, glucose, triglycerides, and cholesterol parameters obtained a significance value of 00,759; 0,983; 0,160; 0,994; 0,413; 0,797; 0,318; and 0,262, and based on the true value target values of SGOT, SGPT, creatinine, BUN, glucose, uric acid, triglycerides, and cholesterol parameters obtained a significance value of 0,70; 0,973; It is concluded that there is no significant difference in VIS value between homemade and commercial lyophilized serum, so homemade lyophilized serum can be used as an option for control material to replace commercial serum for laboratory quality assurance.